METHODOLOGY OF TEACHING THE “PRACTICE OF TEACHING FOREIGN LANGUAGE” BASED ON BLENDED LEARNING TECHNOLOGIES AT THE PROFESSIONAL DEVELOPMENT COURSES - Giyasova , Umida Erkinovna (Educational Research in Universal Sciences, 2023)
The paper is devoted to the issue of methodology of teaching the “practice of teaching foreign language” based on blended learning technologies at the professional development courses. Such aspects as linguistic, psychological and methodological components in teaching foreign languages, using ICT, the efficiency of teaching foreign language by means of blended learning technologies at the professional development courses for higher educational institutions’ teachers have been discussed in the article. Based on the qualification requirements and needs of the “Practice of teaching foreign language” module, the distance learning courses based on the blended learning technologies of the “English for Special Purposes (ESP)” module were developed and supplemented with the necessary methodological materials.